(3cJGH GdQhMs - (3Wg GdOejGWj , Wg Hf eMeO bWQjg GdOejGWj,J (B1325 (3g` s ((3eMeO Hf eMehO Hf eSYhO Hf eMeO GdMfai s)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdYGde CeG HYO agPG cJGH eTJed YdieSGFd ai GdQhM heYGfjgG s
(3BNQgG (B:s
(3hge jMSHhf Cfge jMSfhf UfYkG Efg SejY GdOYGA hCgd GdQLGA s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B44s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1421s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs